The Impact of Pesticides on the Antioxidant System of Apis Mellifera Bees - A Systematic Review - Iloran R. C. Moreira; Guilherme Duarte F. Souza; Aline Astolfi; Isabella Cristina C. Lippi; Jaine L. Scheffer; Renato Agostinho Arruda; Suellen Matos da Silva; Ricardo de Oliveira Orsi (Sociobiology)
During foraging, bees come into contact with different pesticides when collecting crop resources, affecting not only the bees but also the entire colony, resulting in damage to the antioxidant and immune system and a reduction in the number of individuals in the colony. An efficient antioxidant system is essential for bees due to their high metabolic rate, which produces significant free radicals under physiological conditions. Antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione S-transferase (GST) are essential for combating oxidative stress. To better understand these effects, we adopted a systematic approach to review existing research on the potential impacts of pesticides on the antioxidant system of honey bees. Therefore, this review aims to list the papers published between 2020-2023 and show the effects of pesticides (insecticides, herbicides, and fungicides) on the antioxidant system of honey bees, focusing on the enzymes CAT, SOD, and GST. A total of 19 articles were found that met the criteria of this review, of which approximately 89% of the experiments were conducted in the laboratory and only 11% in the field. All of the studies assessed the exposure of bees to pesticides through ingestion, highlighting the lack of studies using the contact exposure method and conducting experiments in the field. It was, therefore, possible to suggest several points for future research to improve the current knowledge base on the potential effects of pesticides on honey bees.